Digitalisasi UMKM Toko Genteng PD. Sentra Atap : Solusi Inovatif untuk Meningkatkan Daya Saing di Era Pasar Online - Hartono, Ardhit Wiro; Adiba; Makhrisyafrisal, Mohammad; Hidayat, Arif (CV ODIS, 2025)
The rapid development of digital technology has significantly transformed the business landscape, including the Micro, Small, and Medium Enterprises (MSMEs) sector. This study aims to analyze the implementation of digitalization strategies at PD. Sentra Atap, a traditional roof tile store, to enhance its competitiveness in the growing online market. Employing a qualitative approach through observation and interviews, the study finds that the lack of technological adoption is the primary obstacle. Proposed solutions include creating a website, utilizing social media, integrating with marketplaces, and providing digital training for business actors. These findings are expected to serve as a practical reference for similar MSMEs in embracing digital transformation.